PERAN GOOD CORPORATE GOVERNANCE SEBAGAI MEDIASI PENGARUH KINERJA KEUANGAN TERHADAP KEBIJAKAN DIVIDEN - andi kartika; Cahyani Nuswandari (Faculty of Economics and Business | Universitas Diponegoro, 2020)
This study aims to examine the role of mediating good corporate governance the effect of the financial performance of corporate to the dividend policy. The financial performance under study includes ROA, CR, DER, Growth, and FCF. The population of this study are companies that included in the CGPI ranking and listed on the Indonesia Stock Exchange, with the Purposive Sampling technique, by corporate that shares the benefist such as dividen to shareholders on the year of CGPI’s ranking, corporate that stated the financial statements per December 31st in IDR currency. The analysis technique used was to use multiple regression and path analysis. The results of this study indicate that ROA has a significant negative effect on the DPR, CR, FCF and GCG has a significant positive effect to the DPR, DER, and Growth does not have any effect to the DPR. Growth has a significant negative effect to the DPR. ROA, and CR have no negative effect on GCG, DER has no positive effect on GCG, Growth has a negative effect on GCG, FCF has a significant positive effect on GCG, meanwhile ROA, CR, DER does not have any effect to GCG. GCG is able to mediating the effect of FCF to the DPR.